PERAN OTORITAS JASA KEUANGAN (OJK) DALAM PENGAWASAN DAN PENCEGAHAN INVESTASI ILEGAL DI INDONESIA - Rohmatun, Rohmatun; Argarinjani, Restu; Panggiarti, Endang Kartini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
OJK is an institution that is tasked and responsible for supervising and preventing illegal investments, as stipulated in Law No. 21 of 2011 concerning OJK. OJK plays a role in overseeing all activities engaged in the financial services sector, one of which is illegal investment, so it is important for OJK to provide direction and legal protection to the wider community, especially those who have or will invest in the financial services sector, as well as people who invest in Indonesia. This research is important for OJK to provide knowledge about these investments. This research was conducted using the library law method. Based on the results of the research, it is found that according to Law Number 21 of 2011, OJK is an institution that has enormous authority, but at the same time it is also an institution that has the task of regulating and supervising all financial services institutions in Indonesia and the role of the prevention and supervision of the Financial Services Authority on illegal investments has had a positive influence on investment activities in Indonesia, starting with regulation and supervision as well as several other prevention and prosecution roles.